Hubungan Pengetahuan Tentang Demam Berdarah dengan Perilaku Pencegahan (DBD) di wilayah Kerja Puskesmas Jekan Raya Kota Palangka Raya Tahun 2022: Knowledge About Dengue Fever with Preventive Behavior (DBD) in the Region Jekan Raya City Puskesmas Work Palangka Raya 2022 - Kevin Sevdo; Mariaty A. Sangkai; Melisa Frisilia (Jurnal Surya Medika (JSM), 2023)
Dengue Hemorrhagic Fever (DHF) is a vector-borne disease. The vector carriers of the dengue virus are mostly mosquitoes of the Aedes aegypti and Aedes albopictu types. The community's level of knowledge about Dengue Hemorrhagic Fever in the Jekan Raya Health Center's Working Area is in the low category (47.5%) Community Behaviors About Dengue Hemorrhagic Fever Prevention In the Jekan Raya Community Health Center Work Area, most of the community's behavior is categorized as negative (55%.). The design of this research is an analytic survey with a cross sectional approach, the population in this study is all the people who visit the Jekan Raya Public Health Center by 40 people. The results of this study indicate that Agar can contribute to training and organizing outreach activities to increase public knowledge about DHF. And this research becomes reading material and literature for the development of health sciences and becomes additional information for all parties. Knowledge of Dengue Hemorrhagic Fever with Preventive Behavior (DHF) in the Work Area of ​​the Jekan Raya Public Health Center, Palangka Raya City.